Does trade openness and financial liberalization foster growth An empirical study of Greek economy - Awojobi, Omotola (Emerald Group Publishing Ltd, 2013)
Purpose - This study aims to provide time series evidence of the economic growth pattern of Greece and explain the hidden impact of its financial liberalization process since 1960, in terms of the links between trade and gross domestic output. Design/methodology/approach - Using time series data covering the period 1960-2009, the author estimates a vector error correction model (VECM) in order to analyze the long-run equilibrium features of proxies for openness and growth in Greece. The author further tests the relationship between financial development and economic growth using the Granger causality hypothesis. Findings - Results from regression estimates find the error correction term (ECT) to be 20.20 for the sampled data. This suggests that there is long-run convergence among financial development, trade openness and domestic output in Greece. This convergence is expected within an average of five cumulative years. Furthermore, the Granger causality test shows that there is a causal relationship between financial development and economic growth, but that financial development has no causal impact on trade in the case of Greece, which is theoretically unexpected. Research limitations/implications - The findings from this study are confined to a short sample observation of 50 years, and also to the proxies the study uses to measure openness and economic growth. Alternative measures of openness could be applied to larger sample data for future investigation on this topic. Practical implications - The author concludes that the financing of economic growth in Greece has not been productive in the industry sector, and that this might have caused the debt crisis of 2009. However, financial development remains the link between trade and growth. When the financial sector is progressive, domestic output increases, and this increase creates production surplus which can be exported. Originality/value - This paper is of value to the academic audience and policy advisers who are interested in the answer to the question what went wrong with Greece? The author uses econometric techniques to prove the inefficiencies of public spending in Greece and the accumulated effects of borrowing to finance growth.
Keywords: Cointegration; Economic growth; Financial liberalization; Trade openness; Granger causality; Greece